Research in the history of economic thought and methodology : including a symposium on public finance in the history of economic thought - Fiorito, Luca; Scheall, Scott; Suprinyak, Carlos Eduardo (Research in the history of economic thought and methodology, 2020)
Research in the History of Economic Thought and Methodology Volume 38A features a symposium on public finance in the history of economic thought co-edited by guest editors Claire Silvant and Javier San Julián Arrupe, as well as general-research essays from Cosma Orsi and John Henry, and a heartfelt obituary by Mattheus Assaf of his friend, Gabriel Oliva, winner of RHETM's first Warren Samuels Prize for Interdisciplinary Research in the History of Economic Thought and Methodology. Including chapters on British public debt in the 19th century, French financial controversies in the mid-1800s, and a thoughtful reflection on the USA's New Deal, this volume is a global exploration of public finance history. For any researcher or student interested in the history of economics, this is an essential read containing the most up-to-date research.